Comparison of success rate of pulpotomy in primary teeth and related factors using formocresol conducted by dental students in Hamedan dental school - Mohammad Esmaeilzadeh; Fahimeh Daneshyar; Zakieh Donyavi; Bashir Tarighi; Shahin Nasiri (Tehran University of Medical Sciences, 2018)
Background and Aims: The structural distinction of primary teeth compared to the permanent teeth leads to a faster penetration of the caries into the pulp, which makes effective treatment necessary. The aim of this study was to determine the success rate of pulpotomy in primary molar teeth and its effective factors using formocresol by students and residents at the department of pediatric dentistry of Hamedan dental school. Materials and Methods: In this cross-sectional study, 113 children who previously had pulpotomy by formecresol in their primary molars (30 children by residents and 83 children by the students) were randomly evaluated based on referral time (at least 12 months after treatment) in terms of clinical and radiographic success rates. Data were analyzed by SPSS20 software using Chi-square and descriptive statistics. Results: The success of the pulpotomy of primary molar teeth was 81.7%. The success rates of the general students and residents were 79.3% and 87.3%, respectively. The percentage of successful pulpotomy was significantly higher in general students at Stainless Steel Crown (S.S.C), second molar in maxilla (P<0.05), but did not have a significant relationship with age and sex (P>0.05). The percentage of pulpotomy success performed by residents did not have a significant correlation with gender, age, type of repair, type of teeth and jaws (P>0.05). In general, the percentage of success in S.S.C, the second molar and maxillary jaw was higher. Also, the success rate of pulpotomy by residents was significantly higher than that of general- students (P<0.05). The highest rates of pulpotomy failure were related to internal analysis. Conclusion: Formocresol pulpotomy using S.S.C in the maxillary second molar teeth had higher success rate.